PWE-159 The effect of natural polymorphism in the promoter of the Helicobacter pylori cytotoxin associated gene, cagA, on cagA transcriptional regulation. (28th May 2012) - Memon, A A; Marx, C K; Robinson, K; Atherton, J C
Abstract : Introduction: Helicobacter pylori persistently colonises the gastric mucosa of almost half the human population. It is the main causative agent of peptic ulcer disease and an important risk factor for gastric carcinoma. One of its major virulence determinants is cytotoxin associated gene A, cagA, and high levels of cagA expression are associated with more severe disease. The functional promoter elements of cagA in the 436 bp cagAB intergenic region have been previously analysed but differences in the promoter region and levels of cagA expression between different H pylori strains have not been studied in detail. We aimed to analyse the cagA promoter region to determine whether naturally occurring polymorphic differences within it contribute to differences in cagA expression level. Methods: Biopsy samples were obtained from 17 patients undergoing routine upper GI endoscopy at the Queen's Medical Centre Nottingham, UK. RNA was extracted directly from biopsies and cagA expression levels were analysed by real-time qPCR. The cagAB intergenic region of all 17 clinical strains were sequenced and aligned using the ClustalW multiple sequence alignment program and ranked in order of cagA transcript levels. A potentially relevant natural mutation was then created artificially by site-directed mutagenesis to prove its importance. Results: A potentially important polymorphism was identified within an imperfect inverted repeat where an A was commonly replaced by a T at position -54. Strains possessing T at this position expressed higher cagA mRNA levels than those with an A (p=0.016). To test whether this was a direct determinant of cagA transcription level, a mutation was engineered at position −54 (T to A) in high transcription strain 83. This resulted in a 30% reduction in cagA transcript level when compared to an isogenic control strain without the change (p=0.073). In the complementary experiment, we engineered an A to T mutation in low transcription strain 126 and this led to a 20% increase in the level of cagA mRNA compared to its isogenic control (p=0.002). Conclusion: Presence of a T at position −54 within the inverted repeat of the cagA promoter region is an important natural determinant of higher levels of cagA transcription. We speculate that this may help explain why only some cagA + H pylori strains cause disease. Competing interests: None declared.